2019
DOI: 10.3390/pharmaceutics11110577
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Successful Stabilization of Poor Glass-Forming Drugs: A Stability-Based Comparison of Mesoporous Silica Versus Hot Melt Extrusion Technologies

Abstract: Amorphous formulation technologies to improve oral absorption of poorly soluble active pharmaceutical ingredients (APIs) have become increasingly prevalent. Currently, polymer-based amorphous formulations manufactured by spray drying, hot melt extrusion (HME), or co-precipitation are most common. However, these technologies have challenges in terms of the successful stabilization of poor glass former compounds in the amorphous form. An alternative approach is mesoporous silica, which stabilizes APIs in non-cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Concerning the stabilization of amorphous API into MPC pores, Ditzinger et al have reported that a mesoporous silica formulation was superior to polymer-based hot melt extrusion (HME) formulations in stabilizing noncrystalline API after one week of storage. 6 The loading of drug into/onto MPC can be done by several methods, which include organic solvent methods such as immersion 7 and spray drying, 8−10 or solvent-free methods including ball milling 11 and HME. 12 ASD research is also expanding beyond conventional binary API/carrier systems to include ternary systems, which have been formulated as API/polymer/polymer, 13−15 API/polymer/ surfactant, 16−18 API/polymer/oligomer, 19−21 and API/polymer/MPC systems, 22−26 with the aim of improving bioavailability and stabilizing the amorphous drug.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the stabilization of amorphous API into MPC pores, Ditzinger et al have reported that a mesoporous silica formulation was superior to polymer-based hot melt extrusion (HME) formulations in stabilizing noncrystalline API after one week of storage. 6 The loading of drug into/onto MPC can be done by several methods, which include organic solvent methods such as immersion 7 and spray drying, 8−10 or solvent-free methods including ball milling 11 and HME. 12 ASD research is also expanding beyond conventional binary API/carrier systems to include ternary systems, which have been formulated as API/polymer/polymer, 13−15 API/polymer/ surfactant, 16−18 API/polymer/oligomer, 19−21 and API/polymer/MPC systems, 22−26 with the aim of improving bioavailability and stabilizing the amorphous drug.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that the use of mesoporous carriers (MPCs), which have a high number of nano-scale pores, as an alternative to polymer carriers in ASD formulations can improve the solubility, dissolution rate, and stability of amorphous API. Concerning the stabilization of amorphous API into MPC pores, Ditzinger et al have reported that a mesoporous silica formulation was superior to polymer-based hot melt extrusion (HME) formulations in stabilizing noncrystalline API after one week of storage . The loading of drug into/onto MPC can be done by several methods, which include organic solvent methods such as immersion and spray drying, or solvent-free methods including ball milling and HME .…”
Section: Introductionmentioning
confidence: 99%
“…It requires a lot of work and time and, frequently, it turns out that the conditions needed for its formation may be difficult to repeat, resulting in problems in manufacturing procedures. 22,23 In this paper, the impact of mesoporous silica (MS) on the physical state of aripiprazole (ARP) will be presented. The use of ARP, an atypical antipsychotic employed in treating various mood and psychotic disorders, as a model drug was essential.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer-based ASDs can satisfy two requirements: suspending the drug in an amorphous form and inhibiting precipitation from supersaturated states [ 8 ]. It has been reported that various pharmaceutical polymers can be used as precipitation inhibitors (PIs) in ASDs, such as PVPVA, polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), hydroxypropyl methylcellulose (HPMC), hydroxypropyl methylcellulose acetate succinate (HPMC-AS), and Eudragit [ 9 ].…”
Section: Introductionmentioning
confidence: 99%